Pengaruh Kualitas Sistem Informasi Akuntansi Berbasis Enterprise Resource Planning (ERP) dan Knowledge terhadap Impact Organisasi di Riau - Irfan, Muhammad; Dp, Emrinaldi Nur; Nasrizal, Nasrizal (Jurnal Ekonomi, 2019)
This paper examines the relationship between the accounting information system quality enterprise resource planning (ERP) based, service information quality, knowledge sharing and training on organizational impacts. The application of information systems and information system services that produce information is measured by perceived usefulness and user satisfaction. The relationship between knowledge sharing and training on personal skills then influences the impact of the organization. This paper investigates whether information systems, organizational culture and end users influence the impact of the organization. The results show that the quality of information and service quality of information systems will improve the information produced, good information affects user satisfaction, information quality does not affect perceived usefulness, perceived usefulness affects end user satisfaction, end-user satisfaction affects personal skills. Knowledge sharing affects personal skills, but training does not affect personal skills, because the application of training focuses only on the practice of using information systems not about producing quality information. Personal skills have an influence on the impact of the organization itself. This finding implies that accounting information systems must be supported by other variables. Therefore, organizations must pay more attention to training in information system implementations based on enterprise resource planing.